Effect of girth class, injury and seasons on ethephon induced gum exudation in Acacia nilotica (L.) Willd. in Chhattisgarh - Raj, Abhishek; Singh, Lalji (Indian Journal of Agroforestry, 2020)
The present study was carried out in naturally growing Acacia nilotica (babul) trees at New Rajdhani area in Raipur district (Chhattisgarh) during rainy, winter and summer season of 2014-2015. Four factors viz. ethephon doses (0, 2 and 4 ml), girth classes (≥ 30.1 to ≤ 50.0 cm and ≥ 50.1 cm), injury (single and double) and seasons (rainy, winter and summer) were subjected to statistical analysis of factorial CRD for understanding their interactions and combined effect on gum exudation. Quality parameter of gum such as pH, moisture content and ash content were 4.5, 15.2% and 2.63%, respectively. The results on quantity of gum exudation (g/tree) in different studied months revealed that exudation per plant was in order: May (5.0) > April (3.88) > March (3.77) > November (2.93) > October (2.60) > February (2.30) > September (2.13) > December (2.05) > January (1.99). Highest quantity (0.727 g/tree) of gum exudation was observed in summer season under the treatment of 4 ml of ethephon in double injury of > 50.1 cm of girth class of babul. In the same season, the quantity of gum was highest (0.690 and 0.625 g/tree) under the treatment of 4 ml of ethephon in > 50.1 cm of girth class and same 4 ml treatment of ethephon in double injury of babul. Seasonally quantity of gum per tree (g/tree) was in the order: summer (4.21) > rainy (2.36) > winter (2.31).